2004
DOI: 10.4141/a03-121
|View full text |Cite
|
Sign up to set email alerts
|

Practical dietary levels of canola oil and tallow have differing effects on gilt and barrow performance and carcass composition

Abstract: , I. L. 2004. Practical dietary levels of canola oil and tallow have differing effects on gilt and barrow performance and carcass composition. Can. J. Anim. Sci. 84: 661-671. Previously we demonstrated that barrows produced leaner carcasses when fed 5% versus 2% canola oil. The present trial was conducted to determine if the same would be true for gilts or when feeding beef tallow (a source of saturated fatty acids). Four diets were fed (2 or 5% canola oil or digestible energy equivalents of tallow), and 27 gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
1
7
3
Order By: Relevance
“…This result was expected and it is consistent with previous reports (Latorre et al, 2003;Suzuki et al, 2003;Dugan et al, 2004). Interaction of sex vs. slaughter weight was observed (P<0.05) on the saturation index, color score, pH 12h of ham and pH 24h of loin.…”
Section: Resultssupporting
confidence: 93%
“…This result was expected and it is consistent with previous reports (Latorre et al, 2003;Suzuki et al, 2003;Dugan et al, 2004). Interaction of sex vs. slaughter weight was observed (P<0.05) on the saturation index, color score, pH 12h of ham and pH 24h of loin.…”
Section: Resultssupporting
confidence: 93%
“…There is little convergence between the results of this study and those of previous studies regarding the effect of gender on pork quality, which are quite variable. However, some responses are consistent across studies, showing that barrows have higher intramuscular fat content than gilts (Candek-Potokar, Monin, & Zlender, 2002;Dugan, Aalhus, Robertson, Rolland, & Larsen, 2004;Ellis, Webb, Avery, & Brown, 1996;Latorre et al, 2003;Suzuki et al, 2003), which was not observed in the present study. The effect of gender on muscle color is not as consistent as its effect on marbling, but higher reflectance values and higher a* and b* values in barrows than in gilts have been reported in some studies (Candek-Potokar et al, 2002;Dugan et al, 2004;Ellis et al, 1996;Latorre et al, 2003).…”
Section: Meat Qualitycontrasting
confidence: 78%
“…Previous studies have not reported any effect on meat colour when flaxseed was included in pig diets (Bee et al, 2008;Corino et al, 2008;Haak, De Smet, Fremaut, Van Walleghem, & Raes, 2008). However, in the present study, the slight increase in pH 48 h (P = 0.022) after the inclusion of flaxseed in the diet may relate to an increased supply of dietary oil, which may have led to a small increase in fatty acid utilisation at the muscle level and a slight inhibition of initial post-mortem glycolytic rates (Dugan, Aalhus, Robertson, Rolland, & Larsen, 2004). Changes in the glycolytic rate could be related to the effects observed in colour and also to the slight decrease in drip loss (P = 0.043) in meat from pigs fed increasing levels of flaxseed.…”
Section: Meat Physicochemical Characteristicscontrasting
confidence: 72%